Interfacial Engineering of Ultrathin Metal Film Transparent Electrode for Flexible Organic Photovoltaic Cells. (13th March 2014) - Zou, Jingyu; Li, Chang‐Zhi; Chang, Chih‐Yu; Yip, Hin‐Lap; Jen, Alex K.‐Y.
<x xml:space="preserve">Abstract</x> A generally applicable method has been developed for fabricating highly transparent ultrathin Ag films on both glass and plastic substrates using the self‐assembled monolayer modified ZnO/Ag/ZnO tri‐layer structure. The resulting films show remarkably low surface roughness with very high transparency (>80% between 400 and 600 nm) and low surface resistance (8.61 Ω/□). With an inverted architecture, the devices based on the SAM modified tri‐layer UTMF electrode show superior performance and mechanical properties than those using ITO electrode on both glass and plastic substrates. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>